Identifying Factors Predictive of Atlantoaxial Fusion Failure in Pediatric Patients: Lessons Learned From a Retrospective Pediatric Craniocervical Society Study. Issue 11 (1st June 2018) - Brockmeyer, Douglas L.; Sivakumar, Walavan; Mazur, Marcus D.; Sayama, Christina M.; Goldstein, Hannah E.; Lew, Sean M.; Hankinson, Todd C.; Anderson, Richard C.E.; Jea, Andrew; Aldana, Philipp R.; Proctor, Mark; Hedequist, Daniel; et al.
Abstract : Study Design: Multicenter retrospective cohort study with multivariate analysis. Objective: To determine factors predictive of posterior atlantoaxial fusion failure in pediatric patients. Summary of Background Data: Fusion rates for pediatric posterior atlantoaxial arthrodesis have been reported to be high in single-center studies; however, factors predictive of surgical non-union have not been identified by a multicenter study. Methods: Clinical and surgical details for all patients who underwent posterior atlantoaxial fusion at seven pediatric spine centers from 1995 to 2014 were retrospectively recorded. The primary outcome was surgical failure, defined as either instrumentation failure or fusion failure seen on either plain x-ray or computed tomography scan. Multiple logistic regression analysis was undertaken to identify clinical and technical factors predictive of surgical failure. Results: One hundred thirty-one patients met the inclusion criteria and were included in the analysis. Successful fusion was seen in 117 (89%) of the patients. Of the 14 (11%) patients with failed fusion, the cause was instrumentation failure in 3 patients (2%) and graft failure in 11 (8%). Multivariate analysis identified Down syndrome as the single factor predictive of fusion failure (odds ratio 14.6, 95% confidence interval [3.7–64.0]). Conclusion: This retrospective analysis of a multicenter cohort demonstrates that although posterior pediatric atlantoaxial fusion success rates are generally high, Down syndrome is a risk factor that significantly predicts the possibility of surgical failure. Level of Evidence: 3